UPAYA MENINGKATKAN KOMPETENSI GURU DALAM MENYUSUN RENCANA PELAKSANAAN PEMBELAJARAN BERBASIS LEARNING CYCLE 7E MELALUI SUPERVISI AKADEMIK - Wati Rahayu (JURNAL PAJAR (Pendidikan dan Pengajaran), 2019)
This study aims to improve teacher competency in developing lesson plans based on the 7E learning cycle through academic supervision. The study was conducted at Air Putih 010 Air Putih Elementary School on 13 teachers conducted for 2 months starting from 26 August to 19 October 2019. This class action research design refers to the research design according to Stephen Kemmis and Mc. Taggart consists of 4 stages in each cycle, including 1) planning, 2) action, 3) observation and 4) reflection. Data analysis through the stages of data collection, data simplification, data presentation, drawing conclusions. The results showed an increase experienced by teachers namely from the first cycle of 66% which is included in the category enough to 83% which is a very good category. Conclusions based on the results and discussion are the competencies of teachers in developing lesson plans based on the 7E learning cycle have increased after academic supervision.